Gendered impacts of the COVID-19 pandemic on the food systems in the Philippines - Romo, Glory Dee A.; Sarmiento, Jon Marx P.; Wahing, Geraliza; Durano, Francis Levi; Traje, Adonis (University of the Philippines, 2023)
All sectors have been introduced to vulnerabilities resulting in lower food availability and accessibility during the COVID-19 pandemic. This study aimed to determine the vulnerability drivers of food systems in the Philippines during the COVID-19 crisis and how the actors were able to adapt to this crisis through a modified resilience causal pathway. Data were gathered from 353 participants (181 farmers, 29 traders/wholesalers/retailers, 61 processors, and 82 who are involved in logistics) nationwide. Of this total number of participants, 143 were male; 207 were female; and three were Lesbian, Gay, Bisexual, Transgender, and Intersex (LGBTI). The findings show that food systems were highly disrupted due to the COVID-19 crisis. Gendered vulnerabilities in the food system were reflected in the following issues: (i) supply and quality issues, caused by increase in prices of material inputs, increase in operational costs, limited transportation, and decrease in human resource availability causing businesses to suspend operations; (ii) income and profit issues such as loss of jobs, decrease in food demand, and additional expenses for COVID-19 safety and prevention; (iii) financial issues such as the use of family/business savings and increase in formal and informal debt; (iv) biological and environmental issues of health concerns, and fear of getting and being exposed to COVID-19 virus; (v) management issues like adjustments made to adapt to the new normal; and (vi) policy and regulatory issues such as difficulty in purchasing and distributing food products due to travel restrictions, working guidelines, and travel requirements. Consequently, various actions were taken by the stakeholders to adapt to these vulnerabilities.